Вплив медіатексту на життя сучасних українців - Тельнова, А. А. (ХНУРЕ, 2022)
This article focuses on assessing the effectiveness of media text as an influence on civic opinion. The main characteristics and properties of media language, ways, and measures of its manipulation over citizens are considered.